Stakeholder satisfaction and sustainable success - Fonseca, Luís (2011)
The relationship between Stakeholder Satisfaction and Organizational Sustainable Growth and Success is investigated focusing on the importance of a firm’s relationships with critical stakeholders that may lead to better performance, as organizations while integrating business and societal considerations create value for their stakeholders. Framed on Stakeholder Theory an online survey was administered to Managers of Portuguese organizations with certified management systems by APCER. The findings suggest that Competitive position is strongly correlated with Shareholders, Suppliers and Partners, Employees and Customers satisfaction, legitimating Freemans Stakeholder Theory. In an overall final remark, the importance of Shareholders, Partners/Suppliers, Employees and Customers satisfaction for organisational Sustainable Success is highlighted in this study results.